«Massacre, pillage and destruction»: social aspects of the Mexican revolution from a Colombian perspective, 1910-1917 - Cortés Guerrero, José David (Universidad Pedagógica y Tecnológica de Colombia, 2021)
This article shows how the Mexican Revolution, between 1910 and 1917, was interpreted, as regards social aspects, in Colombia. This means showinq the beliefs that were created in three specific points: the social causes of the revolution, its social leaders, in particular Pancho Villa and Emiliano Zapata, and the people in arms. In the last two, pejorative images of the revolution are observed, with the objective of delegitimizing any grievance of the popular sectors. The interpretation and images elaborated about the revolution, in Colombia, were a consequence of the fear of its spreading and of the bad example it set, and therefore, it is observed that the revolution was seen, mainly, as a confrontation where massacres, destruction and pillage ruled.